PENGARUH PEMBERIAN BUAH NAGA TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER III DI KLINIK BIDAN SRI WAHYUNI KECAMATAN UJUNG PADANG KABUPATEN SIMALUNGUN TAHUN 2020 - Desideria Yosepha Ginting; Layari Tarigan; Susi Endriyana (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
ABSTRACT Anaemia or often referred to as lack of blood is a condition in which the number of red blood cells decreases and results in insufficient oxygen-carrying capacity to meet the body's physiological needs. Problems that arise include an increase in heart rate due to the body trying to provide more oxygen to the tissues, an increase in respiratory rate as the body tries to provide more oxygen to the blood, dizziness due to lack of blood to the brain, feeling tired due to increased oxygenation of various organs including the heart muscle. and skeletal, pale skin due to reduced oxygenation, nausea due to decreased gastrointestinal blood flow and central nervous system, decreased hair and skin quality. Overcoming complaints of anaemia non-pharmacological can be done with dragon fruit. The purpose of this study was to determine the effectiveness of dragon fruit in dealing with complaints of anaemia in the Sri Wahyuni ​​clinic, Ujung Padang sub-district, Simalungun district in 2020. This study used a quantitative method, with a quasi-experimental design with a control time-series design. The population of this study were pregnant women who experienced symptoms of anaemia at the Sri Wahyuni ​​Clinic, Ujung Padang District, Simalungun Regency. The sample selection using purposive sampling of 14 people, 7 people were given intervention and 7 people as controls. The results of the study using the Wilcoxon sign rank test showed that the results for the group given pre and post-intervention p-value 0.026 <0.05. The results of the study using the Wilcoxon sign rank test showed that the control p-value was 0.000 <0.05. The conclusion is that there are differences in the two groups after being given dragon fruit in overcoming complaints of anaemia.